Sound Unbound: Sampling Digital Music and Culture - Miller, Paul D. (London MIT Press, 2008)
Sound Unbound: Sampling Digital Music and Culture, edited by Paul D. Miller aka DJ Spooky that Subliminal Kid foreword by Cory Doctorowintroduction by Steve ReichIf Rhythm Science was about the flow of things, Sound Unbound is about the remix--how music, art, and literature have blurred the lines between what an artist can do and what a composer can create. In Sound Unbound, Rhythm Science author Paul Miller aka DJ Spooky that Subliminal Kid asks artists to describe their work and compositional strategies in their own words. These are reports from the front lines on the role of sound and digital media in an information-based society. The topics are as diverse as the contributors: composer Steve Reich offers a memoir of his life with technology, from tape loops to video opera; Miller himself considers sampling and civilization; novelist Jonathan Lethem writes about appropriation and plagiarism; science fiction writer Bruce Sterling looks at dead media; Ron Eglash examines racial signifiers in electrical engineering; media activist Naeem Mohaiemen explores the influence of Islam on hip hop; rapper Chuck D contributes "Three Pieces"; musician Brian Eno explores the sound and history of bells; Hans Ulrich Obrist and Philippe Parreno interview composer-conductor Pierre Boulez; and much more. "Press 'play,'" Miller writes, "and this anthology says 'here goes.'" The groundbreaking mix CD that accompanies the book features Nam Jun Paik, the Dada Movement, John Cage, Sonic Youth, and many other examples of avant-garde music. Most of the CD's content comes from the archives of Sub Rosa, a legendary record label that has been the benchmark for archival sounds since the beginnings of electronic music.Paul D. Miller aka DJ Spooky that Subliminal Kid is a conceptual artist, writer, and musician living and working in New York City. His artwork has appeared in the Whitney Biennial, the Venice Biennale for Architecture, the Andy Warhol Museum, and many other venues. His written work has appeared in such publications as the Village Voice and Artforum. He is an editor of the magazine 21c (www.21cmagazine.com) and the author of Rhythm Science (MIT Press, 2004).Contributors David Allenby, Pierre Boulez, Catherine Corman, Chuck D, Erik Davis, Scott De Lahunta, Manuel DeLanda, Cory Doctorow, Eveline Domnitch, Frances Dyson, Ron Eglash, Brian Eno, Dmitry Gelfand, Dick Hebdige, Lee Hirsch, Vijay Iyer, Ken Jordan, Douglas Kahn, Daphne Keller, Beryl Korot, Jaron Lanier, Joseph Lanza, Jonathan Lethem, Carlo McCormick, Paul D. Miller aka DJ Spooky that Subliminal Kid, Moby, Naeem Mohaiemen, Alondra Nelson, Keith and Mendi Obadike, Hans Ulrich Obrist, Pauline Oliveros, Philippe Parreno, Ibrahim Quaraishi, Steve Reich, Simon Reynolds, Scanner aka Robin Rimbaud, Nadine Robinson, Daniel Bernard Roumain (DBR), Alex Steinweiss, Bruce Sterling, Lucy Walker, Saul Williams, Jeff E. Winner